2015
DOI: 10.1088/0953-2048/28/8/085017
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the critical current of intrinsic Josephson junctions by carrier injection

Abstract: We present a study of the doping effect by carrier injection of high-T c superconducting Bi-based whiskers. The current was injected in the c-axis direction, i.e., perpendicular to the superconducting planes. Superconducting properties were investigated systematically as a function of the doping level. The doping level of one and the same sample was changed by current injection in very small steps from an underdoped state up to a slightly overdoped state. We have observed that T c versus log (j c ) exhibits a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…It can be clearly seen that the carrier injection effect caused an increase of I c , while Δ s decreased with increased doping level. This increase of I c is in good agreement with our earlier study [30] and also with several studies in the literature indicating that the c-axis critical current density, J c , changes exponentially with the doping level or oxygen excess δ [31][32][33]. Moreover, we observe that the J c values that can be calculated from figure 8(b) lie in the range J c = (4.7-6.4) × 10 2 A cm −2 , which all fall into the underdoped regime [29].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It can be clearly seen that the carrier injection effect caused an increase of I c , while Δ s decreased with increased doping level. This increase of I c is in good agreement with our earlier study [30] and also with several studies in the literature indicating that the c-axis critical current density, J c , changes exponentially with the doping level or oxygen excess δ [31][32][33]. Moreover, we observe that the J c values that can be calculated from figure 8(b) lie in the range J c = (4.7-6.4) × 10 2 A cm −2 , which all fall into the underdoped regime [29].…”
Section: Resultssupporting
confidence: 94%
“…Doping of the crystal stack by carrier injection led to an increase of ∼24% for the I c of the IJJs, but the doping inhomogeneity for the different junctions was preserved. The doping inhomogeneity among the junctions in the underdoped regime is a well-known scenario, and it gradually disappears as the doping rate approaches the overdoped regime [7,30]. Additionally, it can be seen that the voltage value, at which superconductivity disappeared, shifted to lower values.…”
Section: Resultsmentioning
confidence: 95%
“…For small stacks, with lateral dimensions of a few μm consisting of some 10 IJJs, it was shown that the charge carrier concentration can be changed reversibly in situ by heavy current injection [62][63][64][65]. The effect is different from electromigration and oxygen diffusion and presumably related to the (un)filling of charge traps in the insulating layers [62,63].…”
Section: Introductionmentioning
confidence: 99%